145k views
2 votes
Simplify completely. show your work. thank you for your help!​

Simplify completely. show your work. thank you for your help!​-example-1

2 Answers

1 vote

Answer:

6
√(15)

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab) , then


√(60)

=
√(4(15))

=
√(4) ×
√(15) = 2
√(15) thus

3
√(60)

= 3 × 2
√(15)

= 6
√(15)

User Sajan Rana
by
4.6k points
2 votes

Answer:6 or decimal 23.23790

Explanation:

the prime factorization of 60: 2^2 * 3 * 5

=
3\sqrt{2^(2) }

User Darryn Hosking
by
4.8k points